PENGARUH KEMUDAHAN DAN KEAMANAN TERHADAP KEPUASAN PENGGUNA SHOPEE PAY LATER DI KOTA BEKASI - Efrialdi Sulaeman; Arief Syah Safrianto (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2025)
The porpose to analyze the influence of convenience and Security on Shopee Pay Later user satisfaction in Bekasi. This research is included in the category of causal associative research using a quantitative approach. The population in this study were Shopee Pay Later users in Bekasi. The sampling technique used incidental sampling technique. The analytical method uses simultaneous and partially linear regression analysis. The results of the research show that in simultaneous and partially ways convenience and security have a positive and significant effect on on Shopee Pay Later user satisfaction in Bekasi